The putative siderophore‐interacting protein from Vibrio anguillarum: protein production, analysis, crystallization and X‐ray crystallographic studies. Issue 5 (2nd May 2018) - Han, Yu; Zang, Kun; Liu, Changshui; Li, Yingjie; Ma, Qingjun
Abstract : Siderophore‐interacting proteins (SIPs) can reduce ferric iron to ferrous iron and cause iron to be released from the ferric siderophore complex. The SIP from Vibrio anguillarum 775 has been expressed, purified and crystallized. The crystal diffracted to 1.113 Å resolution, which is the highest resolution so far observed for a member of the SIP family. Abstract : Siderophore‐interacting proteins (SIPs) play an important role in iron acquisition in many bacteria. SIPs release iron from the internalized ferric siderophore complex by reducing ferric iron to ferrous iron, but how the iron is reduced is not well understood. Here, a sip gene was identified in the genome of Vibrio anguillarum 775. To further understand the catalytic mechanism of the protein, the SIP was overexpressed in Escherichia coli Rosetta (DE3) cells, purified and crystallized for X‐ray diffraction analysis. The crystal diffracted to 1.113 Å resolution and belonged to space group P 21, with unit‐cell parameters a  = 64.63, b = 58.47, c = 70.65 Å, β = 114.19°.